Idol anxiety - Tugendhaft, Aaron (Stanford University Press, 2011)
What's wrong with images? / Jan Assmann -- The Christian critique of idolatry / Marc Fumaroli -- The painter's breath and concepts of idol anxiety in Islamic art / Mika Natif -- Idolatry : Nietzsche, Blake, and Poussin / W.J.T. Mitchell -- Dreadful beauty and the undoing of adulation in the work of Kara Walker and Michael Ray Charles / Rachael Ziady DeLue -- Iconoclasm and real space / David Summers -- How many ways can you idolize a song? / Rose Rosengard Subotnik -- Iconoclasm and the sublime : two implicit religious discourses in art history / James Elkins -- What we see and what appears / Jean-Luc Marion -- On Heidegger, the idol, and the work of the work of art / Daniel Doneson -- Beyond instrumentalism and voluntarism : idol anxiety and the awakening of a philosophical mood / Daniel Silver